Tracking of Point Defects in the Full Compositional Range of AlGaN via Photoluminescence Spectroscopy. Issue 8 (9th December 2022) - Hyun Kim, Ji; Bagheri, Pegah; Kirste, Ronny; Reddy, Pramod; Collazo, Ramón; Sitar, Zlatko
Abstract : A comprehensive energy map as a function of AlGaN composition over the whole alloy range is presented for commonly observed point defects in nominally intrinsic, n‐, and p‐doped material. The map covers intentional and unintentional impurities (CN, MgIII ), vacancies (VIII, VN ), passivating complexes (H), and self‐compensating complexes. The tracking of these defects is crucial to understand their impact on optical and electrical properties as well as for their mitigation. Abstract : A comprehensive energy map as a function of AlGaN composition over the whole alloy range is presented for commonly observed point defects in nominally intrinsic, n‐, and p‐doped material.